Design of computer experiments applied to modeling of compliant mechanisms for real-time control (2013)
This article discusses the use of design of computer experiments (DOCE) (i.e., experiments run with a computer model to find how a set of inputs affects a set of outputs) to obtain a force–displacement meta-model (i.e., a mathematical equation that summarizes and aids in analyz-ing the input–output data of a DOCE) of compliant mechanisms (CMs) -- The procedure discussed produces a force–displacement meta-model, or closed analytic vector function, that aims to control CMs in real-time -- In our work, the factorial and space-filling DOCE meta-model of CMs is supported by finite element analysis (FEA) -- The protocol discussed is used to model the HexFlex mechanism functioning under quasi-static conditions -- The HexFlex is a parallel CM for nano-manipulation that allows six degrees of freedom (x, y, z, hx, hy, hz) of its moving platform -- In the multi-linear model fit of the HexFlex, the products or inter-actions proved to be negligible, yielding a linear model (i.e.,linear in the inputs) for the operating range -- The accuracy of the meta-model was calculated by conducting a set of computer experiments with random uniform distribution of the input forces -- Three error criteria were recorded comparing the meta-model prediction with respect to the results of the FEA experiments by determining: (1) maximum of the absolute value of the error, (2) relative error, and (3) root mean square error -- The maximum errors of our model are lower than high-precision manufacturing tolerances and are also lower than those reported by other researchers who have tried to fit meta-models to the HexFlex mechanism